Army of evil : a history of the SS - Weale, Adrian (New American Library, 2012)
The most loyal and ruthless enforcers of the Third Reich began as a small squad of political thugs. Yet by the end of 1935, the SS had taken control of all police and internal security duties in Germany--ranging from local village "gendarmes" all the way up to the secret political police and the Gestapo. And by 1944, the militarized Waffen-SS had more than eight hundred thousand men serving in the field, rivaling even Germany's regular armed forces, the Wehrmacht. Here, author Adrian Weale delves into materials not previously available, including recently released intelligence files and never-before published photographs. Going beyond the myths and characterizations, this comprehensive account reveals the reality of the SS as a cadre of unwavering political fanatics and power-seeking opportunists who slavishly followed an ideology that disdained traditional morality--an ideology that they were prepared to implement to the utmost murderous extreme, which ultimately resulted in the Holocaust.--From publisher description.